Hubungan Antara Agama dan Sains - Heri Taufik Ismail; Irawan Irawan; Tedi Priatna (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The main material for writing this article comes from the routine recitation of Ngaji Filsafat held at the Jendral Sudirman Mosque in Yogyakarta on Wednesday, December 13, 2023 with Dr. Fahruddin Faiz, M.Ag. The purpose of writing this article is to find out the extent of the relationship between religion and science. The relationship between religion and science is a complementary relationship. How science can only detect things that are visible to the eye, realistic, musyahadah. Meanwhile, religion, in addition to being able to detect things that are musyahadah, is also able to know the reality of the unseen. In this life, humans cannot be separated from these two things. So that's when humans don't just feel enough with science, humans need religion too. Vice versa, when humans only rely on the supernatural, humans will find it difficult to overcome the problems that occur in everyday life. As was the case in 2019 when a pandemic occurred. Then science played an important role at that time. Although not a few of the religionists who “surrender” to God's destiny. Religion and science are both fitrah, a very basic/basaliy soul urge. If there is a difference between religion and science it is because the footing is different. A scientist is open, will seek and search for new theories according to need. While religion has crowned itself as the absolute/final truth. It needs to be said that science and religion are both interpretations. Science interprets real phenomena, the reality of the universe, while religion interprets God's verses, religious texts. From this, science and religion can complement each other and there is a meeting point.